EFEKTIVITAS MEDIA SOSIAL SEBAGAI MEDIA SOSIAL SEBAGAI MEDIA PROMOSI BERAS PANDANWANGI CENTER - Malia, Rosda; Kautsar, Fahma Nurul (Universitas Suryakancana, 2024)
Social media is widely used by people because it is easy to use and does not require a lot of money. Promotion is one of the ways used to increase sales volume. Pandanwangi Center is one of the agencies that conducts promotions on social media. Promotion effectiveness is measured by the AIDA concept (Attention, Interest, Desire, Action). This study aims to: (1) identify the characteristics of social media as a promotional medium for Pandanwangi Center Rice, (2) analyze the effectiveness of social media as a promotional medium for Pandanwagi Center Rice. The research was conducted at Pandanwangi Center, Cianjur Regency, from January 2023 to July 2023. The analysis method used is qualitative descriptive analysis. Taking respondents with non-probability sampling with Purposive technique totaling 40 people. The results showed that: (1) social media characteristics: (a) Pandanwangi Center does not form a group, (b) The information conveyed by Pandanwangi Center is clear, (c) Pandanwangi's social media archive is considered clear, (d) the interaction carried out by Pandanwangi Center is considered good, (e) The content delivered is very effective, (2) respondents agree that social media is less effective as a promotional medium with details of each stage: (a) respondents agreed at the attention stage, (b) respondents agreed at the interest stage, (c) respondents (67.5%) agreed at the stage of having a desire, (d) respondents (57.56%) disagreed to make a purchase (action).